Методологічні засади реформування військової освіти в Україні - Панфілов, О. Ю. (НТУ "ХПІ", 2009)
From general methodological positions the problems of the modern system of education are analyzed. The strategic tasks placed before the system of formation in Ukraine are formulated. On the basis of the military education state analysis methodological principles of its reformation guaranteing quality of preparation of officers are offered
Keywords: триступенева структура вищої освіти; кредитно-модульне навчання; модульна система викладання дисциплін; рейтингова система оцінювання; індивідуальний навчальний план; інформаційна культура